Hypertension: comparison of drug and non-drug treatments. Issue 6328 (22nd May 1982) - Andrews, G; MacMahon, S W; Austin, A; Byrne, D G
Abstract : Thirty-seven reports of the treatment of hypertension by non-pharmacological means were compared with the results of treatment by standard drug regimens. Treatment by drugs produced the greatest lowering of blood pressure. Treatment by weight reduction, yoga, and muscle relaxation each produced smaller, but appreciable, changes in blood pressure biofeedback, and salt restriction were inferior to those of the other regimens and were not significantly different to the effects of placebo treatment. Large comparative trials of pharmacological and non-pharmacological treatments are needed before definite conclusions can be made.